EFEK MORTALITAS DAN PENGHAMBATAN MAKAN BEBERAPA EKSTRAK TUMBUHAN ASAL KABUPATEN MERAUKE, PAPUA TERHADAP LARVA CROCIDOLOMIA PAVONANA (F.) (LEPIDOPTERA: CRAMBIDAE) - Mendes, Johana Anike; ., Dadang; Ratna, Endang Sri (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2016)
Mortality and feeding inhibition effects of several plant extracts collected from Merauke Distric, Papua againstÂ Crocidolomia pavonana (F.) larvae (Lepidoptera: Crambidae). The objective of this research was to study mortality and feeding inhibition effects of several plants extract species collected from Merauke District Papua as botanical insecticides against Crocidolomia pavonana larvae. Seven plants used in the research were Areca catechu seeds (Arecaceae), Eucalyptus pellita tree barks (Myrtaceae), Myrmecodia pendans tubers (Rubiaceae), Piper aduncum fruits (Piperaceae), Piper betle leaves (Piperaceae), Pandanus conoideus fruits (Pandanaceae), and Zingiber officinale rhizomes (Zingiberaceae). Each plant extract was tested to 2nd instar C. pavonana larvae. The insecticidal activities were assessed including mortality and feeding inhibition activities. Extract concentrations for mortality tests using topical application method were 0,1%, 0,5%, 1%, 2%, and control, while extract concentrations for feeding inhibition tests using choice and no choice methods were 0,25%, 0,5%, 1%, 2%, and control. Each treatment was introduced to ten C. pavonana larvae and replicated five times. The results showed that P. aduncum and P. conoideus fruits extracts gave 100% mortality at 2% rate. Extract of P. betle leaf at 2% rate totally inhibited feeding activity of larvae (100%) using choice method, while extract of Z. officinale rhizome at 2% rate resulted in moderate feeding inhibition effect (75%) using no choice method.Â